2012
DOI: 10.1111/j.1574-6968.2012.02553.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory systems controlling motility and gene transfer agent production and release in Rhodobacter capsulatus

Abstract: Production of the gene transfer agent of Rhodobacter capsulatus, RcGTA, is dependent upon several cellular regulatory systems, including a putative phosphorelay involving the CtrA and CckA proteins. These proteins are also involved in flagellar motility in R. capsulatus. The interactions of proteins in this system are best understood in Caulobacter crescentus where CtrA is activated by phosphorylation by the CckA‐ChpT phosphorelay. CtrA~P activity is further controlled by SciP, which represses ctrA transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 41 publications
4
80
1
2
Order By: Relevance
“…A previous study found that the CckA sensor kinase protein is needed for maximal release of RcGTA from WT SB1003 cells (16), and so the possibility of phosphate signal transduction through CckA was investigated. To facilitate the study of RcGTA production and release, we exploited the RcGTA-overproducer phenotype of DE442, which has a higher proportion of cells in the population expressing RcGTA than does SB1003 (14,20).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study found that the CckA sensor kinase protein is needed for maximal release of RcGTA from WT SB1003 cells (16), and so the possibility of phosphate signal transduction through CckA was investigated. To facilitate the study of RcGTA production and release, we exploited the RcGTA-overproducer phenotype of DE442, which has a higher proportion of cells in the population expressing RcGTA than does SB1003 (14,20).…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of ctrA in R. capsulatus severely diminishes RcGTA mRNA levels and transduction frequencies, indicating that CtrA is required for transcription of the gene cluster (18). RcGTA transduction is similarly reduced by disruption of cckA; however, the RcGTA capsid protein is still produced, and so it appears that CckA is not needed for transcription of the RcGTA gene cluster (16,19). Mercer et al (16) recently reported that the CckA protein is needed for release of the RcGTA capsid protein from cells, but it remained unclear how release is blocked and whether the capsid protein that accumulates in ⌬cckA mutant cells comprises functional RcGTA particles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A cellular phosphorelay involving the R. capsulatus response regulator CtrA is also involved, as loss of this response regulator causes a complete loss of transcription of RcGTA structural genes 32,38 . However, the exact mechanism of CtrAmediated regulation remains to be determined 41 . The control of RcGTA gene expression by cellular systems is consistent with the absence of RcGTA induction by treatment with the DNA-damaging agents mitomycin C or ultraviolet light; such induction would indicate that transcription of the RcGTA cluster is controlled by a phage repressor protein, which is not the case.…”
Section: Boxmentioning
confidence: 99%
“…Although R. capsulatus CtrA is essential for both RcGTA production and recipient capability (13,60,62), the RcGTA promoter is activated in Ͻ1% of WT cells in the stationary phase (7,46). In contrast, the essential recipient capability factor (dprA) promoter is expressed in essentially all cells in a population (13), as we found here for ctrA itself (Fig.…”
Section: Wt B10mentioning
confidence: 56%